2017
DOI: 10.1155/2017/9053932
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Contrast Sensitivity Changes in Acute Central Serous Chorioretinopathy

Abstract: Purpose To evaluate contrast sensitivity (CS) changes in acute central serous chorioretinopathy (CSC). Methods Visual acuity (VA), CS, and subretinal fluid (SRF) were evaluated monthly for 6 months. Treatment was considered at 3 months in case of persistent SRF. Results Twelve of 20 eyes (60%) had spontaneous SRF resolution within 4 months. Five of 8 patients with delayed SRF resolution received either focal laser or photodynamic therapy. The CS was impaired in all spatial frequencies at baseline. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…They still complained about the visual disturbance., this study showed similar results of contrast sensitivity loss with other studies in literature. (6,7,8) This shows the importance of measuring the contrast sensitivity along with visual acuity at each visit in the patients in acute onset of central serous chorioretinopathy.…”
Section: Contrast Sensitivity:-mentioning
confidence: 99%
“…They still complained about the visual disturbance., this study showed similar results of contrast sensitivity loss with other studies in literature. (6,7,8) This shows the importance of measuring the contrast sensitivity along with visual acuity at each visit in the patients in acute onset of central serous chorioretinopathy.…”
Section: Contrast Sensitivity:-mentioning
confidence: 99%
“…Previous reports demonstrated that low-contrast visual acuity tests as well as contrast sensitivity function measurements can be useful [ 14 ]. Several studies have reported contrast sensitivity in eyes with CSC [ 10 , 12 , 15 ]. Contrast sensitivity has been reportedly decreased in both eyes with active CSC and eyes with resolved CSC as compared with fellow eyes [ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported contrast sensitivity in eyes with CSC [ 10 , 12 , 15 ]. Contrast sensitivity has been reportedly decreased in both eyes with active CSC and eyes with resolved CSC as compared with fellow eyes [ 12 , 15 ]. Moreover, it has been reported that in eyes with resolved CSC, contrast sensitivity was decreased despite visual acuities being preserved [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF testing allows evaluation of visual performance in the low and middle spatial frequency ranges in addition to high frequency . Numerous ocular diseases and abnormalities affect CSF more than VA . Therefore, eye‐care practitioners may misdiagnose and/or improperly treat patients if CSF is not measured.…”
mentioning
confidence: 99%